BONUS MECHANISMS, TAX AVOIDANCE, AND DIVIDEND POLICY IN RELATION TO EARNINGS SMOOTHING: THE MODERATING ROLE OF FIRM SIZE - Dede Sunaryo (Jurnal Comparative: Ekonomi dan Bisnis, 2026)
Earnings smoothing remains a critical issue in corporate financial reporting, as it may obscure true performance and reduce transparency for stakeholders. In emerging markets such as Indonesia, managerial incentives and financial policies are often linked to earnings management practices, raising concerns for regulators and investors. This study aims to examine the effects of bonus mechanisms, tax avoidance, and dividend policy on income smoothing, with firm size as a moderating variable, in consumer non-cyclical companies listed on the Indonesia Stock Exchange during 2019–2023. The research employs purposive sampling, yielding a sample of nine firms with panel data analyzed using regression techniques in EViews 12. The findings indicate that bonus mechanisms do not significantly influence income smoothing, while tax avoidance and dividend policy positively affect earnings smoothing practices. Furthermore, firm size weakens the relationship between bonus mechanisms and income smoothing but strengthens the effects of tax avoidance and dividend policy. This study contributes to the literature by highlighting the moderating role of firm size in shaping managerial behavior and financial policy impacts on earnings smoothing. The results provide practical implications for regulators and investors in evaluating corporate governance effectiveness and ensuring financial reporting quality in the Indonesian context.